Late Roman and Migration Period pottery from Cibalae - Roksandić, Danijela (Array, 2014)
Cibalae (today's town of Vinkovci) were situated in Slavonia region in the eastern part of Croatia, and it have been continually inhabited for 8, 000 years now. The most interesting archaeological layer is a layer of Late Antiquity (late 4th century) which according to recent research proves that Cibalae continued to live in the end of this period. This paper will present recent research results, and special attention will be placed on the ceramic material. Besides the typical Roman provincial pottery forms in the late roman layers appears ceramic material that belongs to the 5th and 6th century and can be linked to migrations of German tribes in this area. Due to the insufficient exploration and interpretation of the archaeological material, it is difficult to attribute ethnic elements to this material, but one can discern a difference in a genuine local tradition and new elements among the ceramics used within the settlements during the 5th and 6th centuries on the mentioned area. This primarily refers to the decorating techniques: burnishing and stamping